Author Correction: Jungle Express is a versatile repressor system for tight transcriptional control. Issue 1 (December 2018) - Ruegg, Thomas; Pereira, Jose; Chen, Joseph; DeGiovanni, Andy; Novichkov, Pavel; Mutalik, Vivek; Tomaleri, Giovani; Singer, Steven; Hillson, Nathan; Simmons, Blake; Adams, Paul; Thelen, Michael
In the original version of this Article, an incorrect URL was provided in the Data Availability Statement regarding the deposition of plasmids listed in Supplementary Table 4. The correct URL ishttps://public-registry.jbei.org/folders/378 . This error has been corrected in both the PDF and HTML versions of the Article.